Lateral location of placenta on ultrasound as a predictive test for preeclampsia - Kaku, Ramya; Shivaraju, Pradeep; R., Vimala K.; Lingegowda, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders represent the most common medical complication of pregnancy Pre-eclampsia complicates approximately 2-7% of pregnancies and is a major cause of maternal and perinatal morbidity This has led to the interest in screening. The placenta is located laterally in majority of patients with abnormal flow velocity waveforms. In the light of these observations, we designed a prospective study to find out whether the lateral location of placenta as seen by ultrasound at II and III trimester of gestation can be used to predict the development of preeclampsia. Methods: A prospective observational study was done in PESIMSR, Kuppam, Andhra Pradesh. The aim of the study was to find out whether placental laterality as determined by ultrasound can be used as a predictor of development of gestational hypertension, development of preeclampsia/eclampsia During the study period of November 2013 to November 2014, all antenatal women attending the OPD in II and III trimester without any medical disorders like DM, HTN, renal disease, cardiac disease or smoking, who undergo ultrasound in II and III trimester were included. The location of the placenta was determined by real time ultrasound in II and III trimester. The placenta will be classified as central when it is equally distributed between the right and the left side of the uterus irrespective of anterior, posterior or fundal position. When 75% or more of the placental mass is to one side of the midline, it is classified as unilateral right or left placenta. subjects were followed upto delivery for development of gestational hypertension/ preeclampsia/eclampsia as per the ACOG criteria. Results: 66% patients in the lateral placenta group developed preeclampsia. Only 36%in the central group developed preeclampsia. The association of lateral placenta as a predictor of preeclampsia had a P value of <0.001 which is statistically significant. Incidence of preclampsia is more in primigravidas compared to multigravidas. Most of the pre eclamptics had their onset at 29 – 32 weeks of gestation. Conclusions: The study shows that placental position determined by ultrasonogram in II and III trimester of gestation is an excellent screening tool for the prediction of pre-eclampsia. The test is ideal because it is simple, non-invasive, cost effective and convenient to the women.